Privacy and Security in IOT Cloud-Based Healthcare System - Deepika Dhawan; Faiyaz Ahmad (International Journal of Engineering and Management Research, 2022)
One of humanity's greatest difficulties is health. In the recent decade, healthcare has gotten a lot of attention. Technology is important in healthcare not just for sensory equipment, but also for communication, recording, and display devices. It is crucial to keep track of a variety of medical markers as well as the post-operative days. As a result, the Internet of things has been used in healthcare. The patient monitoring system has recently become one of the most significant breakthroughs due to its superior technology. A current strategy is essential at this time. The underlying problem with the previous method is that in severe cases, health care professionals must be present at the patient’s location to monitor symptoms on a regular basis. To address this problem, health care professionals must develop a patient monitoring system that allows them to monitor their patients remotely. The idea is a mobile based wireless health monitoring system that might provide real-time online information on a patient's physical status. The Raspberry plays a vital role in this project, as are sensors like as temperature, pulse/heart rate, and PIR. These sensors are connected to an Arduino board which reads the sensor data and send it through a serial connection to the Raspberry Pi. The sensor data is now saved in a file on the Pi, which is then uploaded to the cloud over the Internet. Finally, the user app retrieves the data.. The same data is then transferred to the patient and doctor via Firebase to further improve treatment by obtaining patient information in a timely manner.